If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-36=-3s+6s
We move all terms to the left:
-36-(-3s+6s)=0
We add all the numbers together, and all the variables
-(+3s)-36=0
We get rid of parentheses
-3s-36=0
We move all terms containing s to the left, all other terms to the right
-3s=36
s=36/-3
s=-12
| (x/2)+8=8 | | 4(w+7)=36 | | 7d–4d=15 | | 8x+2-3x=14 | | -d/3+13=16 | | 2000^5=x | | 8=2(11+q) | | 1=-y/2 | | -9v–4v=39 | | 2^3z+9=8^2z+1 | | -6d+17=23 | | 0.25x+6=4(x-6) | | q/5=2 | | 38=9a+2 | | p5=0 | | 2=d2–4 | | x^2-9x=-2x-6 | | 3(w+3)=w-4 | | -q2–19=-17 | | x^2-84=2x-4 | | -16x^2+40x+0=9 | | 2x+5=-3x+13 | | 12(3+x)+3x=1.5(x+4)−4.5+2x | | 12x–17=151 | | 1/4p+7=`9 | | 2x/3-1=5x/2+3 | | 25=2x^2-30x | | 122=266-u | | 137=-u+214 | | 8u=45-u | | 24+6y=12y | | -3x+6=-5x+17/3 |